Automated Valuation Model: An Alternative Property Valuation Procedure - Abdul Rahman, Rohana; Buyong, Taher (Journal of Techno-Social, 2012)
Accurate value and fast delivery are the main an objectives when an exercising property valuation. Sales Comparison Method (SCM) is the most popular approach for valuing properties worldwide but the theory is criticized for its subjectivity constrain. Furthermore, the practice of property valuation in Malaysia has remained human intensive tasks which are prone to mistakes and most importantly cannot meet the current demand for fast and accurate valuation. This alternative procedure which also calls automated valuation model (AVM) is invented to produce more efficient valuation. AVM is a mathematically based computer software program that produces an estimate of market value based on market analysis. AVM will follow sound statistical and mathematical modelling practices and be tested for accuracy and uniformity for application. AVMs are not meant to replace valuation professionals; they are tools to aid valuation tasks. Any valuer can just click on the value map and the valuation is done automatically within a minute. This paper proposes an alternative property valuation procedure to make automated valuation possible and subjectivity can be eliminated. The proposed procedure uses precise rules for selecting, adjusting and weighting of comparable. An empirical example is provided. A limited accuracy analysis shows high potential of the procedure as evidenced by a relatively high prediction capability. It is recommended that the procedure be extensively studied.